Panorama de riesgos en los contratos de infraestructura en el litoral Pacifico Chocoano (2020)
The present monograph through the design of the strategic analysis method for a construction company that allows estimating and analyzing the risks in the participation of infrastructure projects in the Colombian Pacific Coast, case of the municipality of Pizarro, Bajo Baudo and Nuquí in the department of Chocó , shows the evolution and application of the risk matrix in public procurement and its impact on unforeseen infrastructure construction works, also presents a documentary analysis from the position of different authors and normative and investigative documents on the issue of causes and consequences of delays and breaches in public works contracts, as well as the identification of business failures and weaknesses of construction companies that have incurred delays and / or breaches in the Colombian Pacific Coast, taking as a reference the case municipalities of Pizarro, Bajo Baudó and Nuqu í in the department of Chocó.